2005
DOI: 10.5194/nhess-5-203-2005
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of the seismic-electromagnetic and acoustic waves caused by seismic and volcano activity

Abstract: Part of Special Issue "Precursory phenomena, seismic hazard evaluation and seismo-tectonic electromagnetic effects" Abstract.Modeling of the spectrum of the seismoelectromagnetic and acoustic waves, caused by seismic and volcanic activity, has been done. This spectrum includes the Electromagnetic Emission (EME, due to fracturing piezoelectrics in rocks) and the Acoustic Emission (AE, caused by the excitation and the nonlinear passage of acoustic waves through the Earth's crust, the atmosphere, and the ionosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…6a). It has been recently shown that only the AWs and AGWs in ULF frequency range (< 0.1 s −1 ) can reach to the F region heights (Koshevaya et al 2005). Thus δ W is expected to vary considerably with frequency in the ionosphere and the spectral features presented above may be modified once this aspect is taken into account.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6a). It has been recently shown that only the AWs and AGWs in ULF frequency range (< 0.1 s −1 ) can reach to the F region heights (Koshevaya et al 2005). Thus δ W is expected to vary considerably with frequency in the ionosphere and the spectral features presented above may be modified once this aspect is taken into account.…”
Section: Resultsmentioning
confidence: 99%
“…These observations indicate the existence of energy flow mechanisms from the lithosphere to the ionosphere. The coupling through AGWs is found to be quite effective (Lognonné et al 1998; Koshevaya et al 2005) due to their excitation by the displacements of the terrestrial surface and their large amplitudes at ionospheric heights (Ahmadov & Kunitsyn 2004). Lognonné et al (1998) have shown that a fraction of about 10 −6 of the seismic energy is injected in the atmosphere for frequency larger than 5 mHz via this channel.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of work has been done by a great number of researchers on the characteristics of ionospheric variations (wave-length, attenuation, velocity and way of propagation (Afraimovich et al, 2002)) according to their nature as well as on the theoretical explanation Rapoport et al, 2004a, b;Koshevaya et al, 2005). Nevertheless in order that TEC variations over a particular site are used as earthquake precursory diagnostic a concrete sense of the interrelation of TEC variations over different sites as well as their respond to the geomagnetic field variations would be of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that similar phenomena are also observed in plastic materials such as epoxy resin [43]. The equation relating the electric field strength E to the parameters of the micro-crack formed takes the form [46]:…”
Section: Microcracks In the Rock Structurementioning
confidence: 53%